THE INFLUENCE OF WHATSAPP ON EMPLOYEE PERFORMANCE AT THE MINISTRY OF RELIGION OFFICE GOWA DISTRICT - Irmayanti Khoiriyah; Muhammad Najib Kasim; A. Muhiddin Daweng (International Journal of Economic Research and Financial Accounting, 2024)
WhatsApp media is not only used for personal interests but also used for things that are for work purposes. WhatsApp communication media has both positive and negative impacts. Paying attention to this, the use of whatsapp on employee performance is important to be studied, seeing from the phenomenon that occurred at the Gowa Regency Ministry of Religious Affairs Office, related to whatsapp communication media, all employees use whatsapp. The fact that researchers found at the research location, almost all employees prefer to use whatsapp social media compared to several other social media, such as telegram, instragram and others. Some of the advantages of whatsapp are the reason why all employees use whatsapp including, whatsapp is more secure because it is end-to-end encrypted so that it does not allow others to read, then there is ease in sharing files and documents so that it is more efficient. The purpose of this study was to determine the effect of whatsapp on employee performance at the Gowa Regency Ministry of Religious Affairs Office. The type of research used is quantitative, which is a research method using numerical data with a sample of 64 respondents and using data analysis techniques: validity and reliability tests, classical assumption tests, simple regression analysis. Based on the results of the t-test sig value which is 0.000 < 0.05, the calculated t value is 10,065 > from the table t value which is 1.670 means that whatsapp has a positive and significant effect on performance variables. Based on the results of research conducted at the stage of data collection, data management, and data analysis regarding the influence of whatsapp on employee performance at the Gowa Regency Ministry of Religious Affairs Office, it can be concluded that the use of whatsapp has a positive effect on employee performance.